The tyranny of distance prevails: HTTP protocol latency and returns to fast fibre internet access network deployment in remote economies - Mark Obren; Bronwyn Howell (International Telecommunications Society (ITS), 2011)
As public policies seek to advance deployment of enhanced broadband infrastructure as a means of acquiring economic advantage, the issue has arisen of the extent that additional economic performance accrues from increases in headline bandwidth speed in locations that are physically remote from the infrastructure hosting time-critical information services. For time-dependent applications, latency (the time delay in accessing data across a network) is correlated with the effective bandwidth (the actual speed of access), and thus impacts upon the economic performance of the application to the user. We extrapolated data for interactive web-based applications from Belshe (2010), where latency was found to substantially reduce the effective bandwidth available to the user of a typical web-based application, to estimate the effective bandwidth over a range of headline bandwidths and latencies typical of web-based transacting patterns in New Zealand. We find that the decreasing returns on effective bandwidth as headline bandwidth increases are further exacerbated by the higher levels of latency experienced as a consequence of New Zealand's distance from the bulk of the global infrastructure supporting web-based applications.The benefits of enhancing headline bandwidth through new forms of faster infrastructure were substantially reduced by the impact of the latencies typically experienced by New Zealand users accessing remote web based applications, and thus the economic benefits expected from investment in infrastructure in accessing enhancing those applications most impacting economic performance is likely to have been exaggerated; providing an insight into a constraint upon cloud computing and other web-enabled information systems.
Keywords: O18; O33; R11; R12; 330; Internet; broadband; fibre-optic cable; regional economic development; HTTP protocol